Analisis Penentuan Harga Pokok Produksi Dengan Metode Job Order Costing Pada UMKM Clean Laundry - Iswardhani, Indri; Sarah, Nulthazam (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the application of the Job Order Costing method in determining the cost of goods sold (COGS) at UMKM Clean Laundry. The Job Order Costing method was chosen due to its ability to allocate costs specifically to each type of order. This research uses a quantitative approach with descriptive analysis, where data was collected through interviews, observations, and documentation at UMKM Clean Laundry. The results of the study show that the application of the Job Order Costing method improves the accuracy of production cost calculations and helps in setting more accurate selling prices. The profit margin for each type of laundry service ranges from 45% to 52%, with Small Bedcover service having the highest margin. Although this method is effective, the main challenge faced is the management of cost recording systems, which still need improvement. Therefore, this study suggests that UMKM improve their cost recording systems and implement technology that can enhance operational efficiency and the accuracy of production cost calculations in the future.